2020
DOI: 10.1166/mex.2020.1654
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin scaffolds embedded with sonic hedgehog/chitosan microspheres for recovery of spinal cord injury in rats

Abstract: Sonic hedgehog (SHH) has been shown to exert a protection on promoting the spinal cord injury (SCI) recovery, but it can’t remain with its biological activity and sustained release at the injury site for long-term application. Herein, fibrin scaffolds embedded with SHH-loaded chitosan (CS) microspheres (SHH/CS) were synthesized and applied to provide protection and regeneration for complete transected spinal cord in rats. Characteristics of fibrin scaffolds embedded with SHH/CS microspheres, histological stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Furthermore, the moderate rate of solidification enables surgeons to conduct injections at a more leisurely pace. Compared to hydrogels, 56 microspheres, 57 , 58 or soft scaffolds, 59 GPCL also exhibited excellent mechanical properties and acted as hard tissue. The mechanical properties of GPCL were found to be similar to those of cancellous bone, and GPCL is capable of acting as a scaffold, 60 providing mechanical support in the tunnel.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the moderate rate of solidification enables surgeons to conduct injections at a more leisurely pace. Compared to hydrogels, 56 microspheres, 57 , 58 or soft scaffolds, 59 GPCL also exhibited excellent mechanical properties and acted as hard tissue. The mechanical properties of GPCL were found to be similar to those of cancellous bone, and GPCL is capable of acting as a scaffold, 60 providing mechanical support in the tunnel.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Yang et al. synthesized SHH-loaded chitosan microspheres (SHH/CS) embedded in fibrin scaffolds and then applied this treatment for the protection and regeneration of completely transverse spinal cord injuries in rats [ 157 ]. The results showed that SHH was able to maintain its biological activity and continue to act on the site of injury, and SHH/CS microsphere-embedded fibrin scaffolds showed good effects in nerve regeneration, tissue cavity prevention, and motor function improvement, compared with the separately wrapped fibrin scaffolds.…”
Section: Microsphere Processing Materialsmentioning
confidence: 99%
“…Vesicles-loaded with SAG (a Smo agonist) immobilised on apatite-coated-PLGA scaffolds were shown to induce osteogenic differentiation of BM-MSCs in vitro and enhanced the healing of size-specific bone-defects in vivo by increasing the expression of Gli1 [ 325 ]. Moreover, Shh-loaded chitosan microspheres encapsulated into fibrin scaffolds is another approach that has been used for modulating Hh signalling to restore stem cell proliferation and enhance regeneration in spinal cord injury [ 326 ].…”
Section: Mechanobiological Design Opportunities For Modelling Hedgeho...mentioning
confidence: 99%